EFFECTIVENESS OF USING PHET VIRTUAL LABORATORIES IN SCHOOL PHYSICS EDUCATION - Durisjanov, Maxmud Jetpisbayevich (SCIENCE and SOCIETY, 2026)
This article examines the use of PhET interactive simulations in teaching physics in secondary schools. The study focuses on the integration of virtual laboratories into lessons using the examples of the 7th grade topic “Heat Phenomena” and the 8th grade topic “Electric Circuits”. The advantages of PhET simulations in overcoming the limitations of traditional school laboratories (lack of equipment, safety issues, and time constraints) are analyzed. The paper also provides recommendations for developing students’ logical thinking and independent research skills through virtual experiments.